Internal and External R&D and Productivity – Evidence from Swedish Firm-Level Data - Karin Bergman (Lund University, School of Economics and Management, Department of Economics, 2011)
This paper uses a panel of Swedish manufacturing firms to examine the effects of internal and external R&D on total factor productivity over the period 1991-2004. The findings give some support to the notion of complementarity between internal and external R&D, especially in industries with high R&D intensities, and suggest that the employees' level of education is important for the firm's capabilities to absorb external R&D. However, external R&D is generally found to have a negative effect on productivity and internal R&D is only significant when not including interaction terms between internal R&D and external R&D or human capital.
Keywords: D24; L24; O32; 330; Internal R&D; external R&D; productivity; Sweden